A study protocol for a pilot randomized controlled trial to evaluate the effectiveness of a gene-based nutrition and lifestyle recommendation for weight management among adults: the MyGeneMyDiet® study - Nacis, Jacus S.; Labrador, Jason Paolo H.; Ronquillo, Diana Glades D.; Rodriguez, Marietta P.; Dablo, Aurora Maria Francesca D.; Frane, Ruby D.; Madrid, Marilou L.; Santos, Noelle Lyn C.; Carrillo, Julianne Janine V.; Fernandez, Mikko Glen; Gonzales, Gerard Bryan L. (Frontiers in Nutrition, 2023)
Introduction: Managing nutrition and lifestyle practices, nutrition phenotypes, and the genome forms the foundation of precision nutrition. Precision nutrition focuses on metabolic variability among individuals, and one approach to achieving its goals is to integrate gene-based nutrition and lifestyle recommendations in nutrition practice. However, scientific evidence proving the effectiveness of such recommendations is limited. This study will examine whether providing nutrition and lifestyle recommendations based on individual genotype can lead to better weight loss, along with reduction in body mass index (BMI), waist circumference, and body fat percentage among overweight and obese adults.A parallel group, single-blind, randomized controlled trial will be conducted. Sixty-two overweight/obese individuals aged 19 to 59 years old will be recruited. Participants will be randomly allocated to either the intervention (n = 31) or the control arm (n =31). Participants in the intervention group will receive the MyGeneMyDiet® Recommendation for Weight Management, a gene-based nutrition and lifestyle recommendation that was developed based on existing evidence of the effects of FTO rs9939609 on body weight, BMI, and physical activity; UCP1 rs1800592 on calorie intake; and TCF7L2 rs7903146 on dietary fat intake. Participants in the control group will receive the standard recommendations for weight management. The primary outcomes will be the differences in weight, BMI, waist circumference, and body fat percentage between arms in both the active phase (six months) and inactive phase (last six months) of the trial. Participants in both arms will be evaluated at baseline and in months 3, 6, 9, and 12.Discussion: To the best of our knowledge, this will be the first gene-based intervention that will adopt a phase of intensive nutrition counseling, followed by a simulation of a free-living state to determine adherence to a gene-based recommendation. This study will contribute to the future implementation of precision nutrition interventions by providing evidence on the effectiveness of a gene-based nutrition and lifestyle recommendation for weight loss.This study was registered with clinicaltrials.gov: NCT05098899 on